Pengaruh Delegation Authority, Kompensasi Insentif dan Disiplin Kerja Terhadap Produktivitas Kerja di PT. Dewi Permata Perkasa - Nurul Hidayah; Nurbaiti Betty (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this study was to determine the results of the Effect of Delegation Authority, Incentive Compensation and Work Discipline on Work Productivity of PT. Dewi Permata Perkasa.Employee Productivity is very important to be maintained, but the problems found in PT. Dewi Permata Perkasa is still not achieving the work targets set by the company. This was allegedly due to the lack of good delegation authority, incentive compensation and employee work discipline. To find this out, this study uses the SEM (Structural Equation Modeling) method that examines the structural relationship with the research model partially.The data used in this study were 200 respondents at PT. Dewi Permata Perkasa. The data obtained is then processed using full Linear Structural Relations (LISREL) 8.8. The results of this study indicate that there is no relationship / significant influence between the latent variable Delegation Authority (DA) on Work Productivity (PK); there is a positive relationship / influence between the latent variable Incentive Compensation (KI) on Work Productivity (PK); and there is no relationship / influence between the latent variable Work Discipline (DK) on Work Productivity (PK).